The role of the annexin A protein family at the maternal–fetal interface - Hu, Jingwen; Chen, Lin; Ruan, Jing; Chen, Xiaoyan (Frontiers in Endocrinology, 2024)
Successful pregnancy requires the tolerance of the maternal immune system for the semi-allogeneic embryo, as well as a synchrony between the receptive endometrium and the competent embryo.Annexin family belongs to calcium-regulated phospholipid-binding protein, which functions as membrane skeleton to stabilize lipid bilayer and participate in a wide range of biological processes in humans. There is an abundance of annexin family at the maternal-fetal interface and exert a crucial role in embryo implantation and the subsequent development of the placenta. Altered expression of annexin family and dysfunction of annexin proteins or polymorphisms of ANXA gene are involved in a range of pregnancy complications. In this review, we summarize the current knowledge of the annexin A protein family at the maternal-fetal interface and its association with female reproductive disorders, suggesting the use of ANXA as the potential therapeutic target in the clinical diagnosis and treatment of pregnancy complications.